Clinical Study of Acupotomy for Knee Osteoarthritis Based on the Meridian-Sinew Theory: A Randomized Controlled Clinical Trial. (18th November 2021) - Hua, Zhijuan; Deng, Han; Tang, Huang; Ruan, Zhizhong; Wang, Pei; Zhang, Min; Ma, Hui; Wang, Ping; Dong, Can; Huang, Zhilan; Hong, Hanqing; Zhou, Quan; et al.
Abstract : This study was performed to compare the effectiveness of acupotomy based on the meridian-sinew theory with acupotomy based on the anatomical theory in the treatment of knee osteoarthritis (KOA). A total of 124 patients with knee osteoarthritis were randomized into the meridian-sinew (MS) group (63 patients) and anatomy group (61 patients). In the MS group, acupotomy based on the meridian-sinew theory was performed. In the anatomy group, acupotomy based on anatomy was applied. Patients were subgrouped by TCM Constitutions. The Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index and visual analog scale (VAS) were used to evaluate treatment effectiveness. The results showed that VAS ( F = 22.61, p < 0.01 ) and WOMAC ( F = 24.84, p < 0.01 ) scores declined with time, and there was no significant difference between the two groups nor subgroups (Yang deficiency subgroup, Yin-Yang harmony subgroup, and the subgroup of the others). A total of 5 patients reported 6 cases of the minor adverse effect, and all patients achieved complete recovery without medical intervention. This study indicates that the effectiveness and safety of acupotomy based on the meridian-sinew theory are equivalent to that of acupotomy based on anatomy in KOA treatment.